Commentaries on Infrastructure - Wanmali, Sudhir; Idachaba, Francis Sulemanu (International Food Policy Research Institute, 1987)
Although important to both planning and performance, infrastructure is not easy to define and is difficult to relate to agricultural development in an integrated manner. It is rarely recognized in the current literature that sectoral allocations, distribution systems, indigenous technical knowledge, and social systems are all integral parts of infrastructure. Its effectiveness and efficiency can be understood only by interdisciplinary analyses.